96 RACIAL DIFFERENCES IN PROSTATE-RELATED DISORDERS IN A MULTIETHNIC COMMUNITY. (1st January 2006) - Jayawardena, S.; Siddiqi, Z.; Kong, K. F.; Sheth, K.; Maini, A.
Abstract : Prostate cancer represents a major health problem worldwide. The aim of this study is to determine if the rate of disease screening plays a major role in prostate cancer development in different ethnic groups. Other factors, including PSA levels, smoking, and size of the prostate glands and different pathological diagnosis are also evaluated in this study. Method: A retrospective study involving 190 patients, who showed either prostate-related symptoms or enlarged prostate glands in routine digital rectal examination (DRE), prostate-specific antigen (PSA) and prostate sonograms were done to evaluate for the size of the gland. Patients with the PSA levels > 4 ng/mL got transrectal prostate biopsy. The age of diagnosis, race, PSA level, and gland size were compared among patients with adenocarcinoma, benign adenomatous hyperplasia (BPH) and chronic prostatitis. Results: In our study there were 35.4% Afro-Americans, 30% whites, and 17.4% Hispanics and Asians each. The mean age of diagnosing patients with prostate cancer was 65.7 years; for BPH and chronic prostatitis it was 64.4 years. Though the whites were diagnosed to have prostate carcinoma 5 years earlier than the Asians and Hispanics and 7 years earlier than the Afro-Americans, there was no statistical significance between the ethnic groups. Comparisons of the PSA levels with the overall size of the prostate gland (p = .0519), age (p = .6182), smoking (p = .025), and the duration of smoking (p = .1292) failed to show any statistical significance. There was a strong positive correlation between disease occurrence and PSA level. Only 11% of the healthy individuals had PSA level of > 10 ng/mL, 36% of patients with BPH, 38% with chronic prostatitis, and 60% of patients with adenocarcinoma (p < .05), conforming that PSA is an important diagnosis marker for prostate abnormalities. Conclusion: We did not find any delay in screening among the ethnic groups, probably due to an increase in awareness of the mortality due to prostate cancer. The incidence of different pathological diagnosis also did not differ among the ethnic groups. Though PSA levels did not correlate with the age, size of the gland, or the smoking, there was a good correlation with patients with adenocarcinoma as compared to patients with BPH or chronic prostatitis.